2015
DOI: 10.1007/s00404-015-3883-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between zinc level and the risk of preeclampsia: a meta-analysis

Abstract: Our analysis indicated that zinc level in preeclampsia patients was significantly lower than that of healthy, pregnant women, especially among the Asian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 24 publications
4
12
0
1
Order By: Relevance
“…With respect to essential metals, we observed a reduction, albeit imprecise, in the risk of preeclampsia associated with an increase in urinary Se. This observation is consistent with the literature, which suggests that essential metals, including Se, may reduce the risk of preeclampsia [16, 17]. In contrast, urinary Cu and Se were associated with lower circulating PlGF levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With respect to essential metals, we observed a reduction, albeit imprecise, in the risk of preeclampsia associated with an increase in urinary Se. This observation is consistent with the literature, which suggests that essential metals, including Se, may reduce the risk of preeclampsia [16, 17]. In contrast, urinary Cu and Se were associated with lower circulating PlGF levels.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported associations between toxic metals, such as cadmium (Cd) and lead (Pb), and an increased risk of preeclampsia [1015]. Alternatively, higher exposure to essential metals, such as selenium (Se) and zinc (Zn), within a recommended range, have been routinely associated with a decreased risk of preeclampsia [16, 17]. Possible mechanisms for these associations include that toxic metals may impair trophoblast invasiveness [1821], generate placental oxidative stress [22], or lead to maternal immunologic abnormalities [23], whereas essential metals have antioxidant properties that may reduce the effect of toxic exposures and promote normal placentation [24].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, "serum zinc concentration was found to decrease significantly in the preeclamptic group compared to normotensive pregnant women. Our results are consistent with earlier reports" 6,10,14 . Zn is an important trace element in metabolism, growth, development, and reproduction.…”
Section: Graph I: Serum Zinc Levels Of Control and Cases Groups Discussionsupporting
confidence: 94%
“…Of the 2444 citations identified, 126 systematic reviews were included in this review. Figure provides details of the review identification and selection process.…”
Section: Resultsmentioning
confidence: 99%